Implementation of summation theorems of Andrews and Gessel-Stanton - Qureshi, Mohd Idris; Rahman Sha, Tafaz Ul (Karagandy University of the name of acad. E.A. Buketov, 2023)
Generalized hypergeometric functions and their natural generalizations in one and several variables appear in many mathematical problems and their applications. Solving partial differential equations encountered in many applied problems of mathematics physics is expressed in terms of such generalized hypergeometric functions. In particular, the Srivastava-Daoust double hypergeometric function (S-D function) has proved its practical utility in representing solutions to a wide range of problems in pure and applied mathematics. In this paper, we introduce two general double-series identities involving bounded sequences of arbitrary complex numbers employing the finite summation theorems of Gessel-Stanton and Andrews for terminating 3F2 hypergeometric series with arguments 3/4 and 4/3, respectively. Using these double-series identities, we establish two reduction formulas for the (S-D function) with arguments z, 3z/4 and z, —4z/3 expressed in terms of two generalized hypergeometric function of arguments proportional to z3 and — z3 respectively. All the results mentioned in the paper are verified numerically using Mathematica Program.
Эндрюс пен Гессель-Стэнтонның косындылау теоремаларын жузеге асыру
Реализация теорем суммирования Эндрюса и Гесселя—Стэнтона
Keywords: Generalized hypergeometric function; Srivastava-Daoust double hypergeometric function; Reduction formulas; Mathematica Program